Systematic analysis of post-treatment soft-tissue edema and seroma on MRI in 177 sarcoma patients. (December 2020) - Sedaghat, Sam; Schmitz, Frederick; Meschede, Jens; Sedaghat, Maya
Abstract: Purpose: To assess post-treatment subcutaneous edema, muscle edema, and seroma in MRI after soft-tissue sarcoma (STS) resection with regard to muscle involvement of STS and therapy. Methods: In all, 177 patients were included and received 1.5-T MRI follow-up examinations after treatment. Post-treatment changes were classified according to type of therapy (therapy 1-surgery; therapy 2-surgery with radiation therapy) and primary tumor localization in soft tissue (localization 1, subcutaneous tissue; localization 2, muscle involvement). Subcutaneous and muscle edema were divided into three grades: grade 0, absence of edema; grade 1, low-to-moderate edema; and grade 2, high-grade edema. Results: The mean age of the patients was 55.7 ± 18.2 years and the mean volume of the resected primary STS was 321.5 cm 3 . After therapy 1 of a sarcoma in localization 1, patients significantly more often showed low-grade subcutaneous tissue edema and an absence of muscle edema (p < 0.001) than high-grade edema. The risk for grade 2 subcutaneous tissue and muscle edema significantly increased with a tumor in localization 2 (RR = 2.58, p = 0.016 and RR = 15, p = 0.0065/RR = 2.05, p = 0.021, respectively) and after therapy 2 (RR = 15, p = 0.0087 and RR = 2.05, p < 0.0001, respectively). Of the patients with sarcoma in localization 2, 88% developed grade 2 muscle edema after therapy 2; 40% of the patients developed post-treatment seroma. The risk for seroma is significantly higher after surgery and radiation therapy than after surgery alone (p < 0.001). Conclusion: High-grade postoperative subcutaneous and muscle edema are significantly associated with muscle involvement of primary STS both in patients with and without radiation therapy. The risk for seroma is significantly higher after surgery with additional radiation therapy than after surgery alone. Highlights: Muscle involvement of primary STS is significantly associated with high-grade post-operative subcutaneous and muscle edema. In subcutaneous localized STS the risk for high-grade soft-tissue edema is significantly lower. The risk for and the mean volume of seroma is significantly higher after surgery with additional radiation therapy.